2012
DOI: 10.5402/2012/519321
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pyelonephritis in Pregnancy: A Retrospective Descriptive Hospital Based-Study

Abstract: Introduction. Pyelonephritis is a common complication of pregnancy. It is also exacerbated by immunocompromised states and also the sickle cell gene. We reviewed this condition in Jamaican women. Method. We did a six year hospital database docket review. We found 102 confirmed cases. Results. Pyelonephritis was found in 0.7% of deliveries. The mean maternal age was 24 ± 5.83 years with 51% primiparity. Most (58.8%) occurred in the second trimester. The main symptoms were loin pain (96.2%) and abdominal pain (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 30 publications
9
44
0
2
Order By: Relevance
“…Similarly, Dawkins et al reported flunk pain as the most common symptom in their study (6). In addition, the right side CVA tenderness was present in most patients (66.7%), the same as reported by Angel et al (14).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Similarly, Dawkins et al reported flunk pain as the most common symptom in their study (6). In addition, the right side CVA tenderness was present in most patients (66.7%), the same as reported by Angel et al (14).…”
Section: Discussionsupporting
confidence: 72%
“…Nowadays, it is well established that pregnant women with pyelonephritis are at increased risk of sepsis, ARDS (acute respiratory distress syndrome) and ICU care requirement compared to non-pregnants with pyelonephritis. On the other hand, studies claimed that pyelonephritis absorbs a considerable proportion of healthcare budgets (12.4 million dollars per year) and causes excessive load of expenses (6,11,12). The advantages of early screening and treatment of asymptotic bacteriuria, especially in gestational period is an undeniable fact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations